2008
DOI: 10.1158/1535-7163.mct-08-0020
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with an endocytically located photosensitizer cause a rapid activation of the mitogen-activated protein kinases extracellular signal-regulated kinase, p38, and c-Jun NH2 terminal kinase with opposing effects on cell survival

Abstract: Photochemical internalization (PCI) is a method for release of endosomally/lysosomally trapped drugs into the cell cytosol. PCI is based on photosensitizers that accumulate in the membranes of endosomes and lysosomes. Light exposure generates reactive oxygen species that cause membrane rupture and subsequently drug release. PCI can be considered as a combination therapy of photodynamic therapy (PDT) and the administrated drug. The present work reports on mitogen-activated protein kinase signaling after PDT wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
4
19
1
1
Order By: Relevance
“…In other studies using various photosensitizers, the role of p38 activation in PDT response appears to be ambiguous [29], [30], [31], [32], [33], [34]. Recently, p38 activation as a death signal has been described for the endocytically located photosensitizer TPPS2a (meso-tetraphenyl-porphine), which is applicable to photochemical internalization, a method used for release of endosomally/lysosomally trapped macromolecular drugs into the cell cytosol to enhance their biological effect in vitro [35]. We can relate our para EG-porphyrin results with these data because they exhibit similar intracellular localization and mechanism involving p38 MAPK activation in the cell death induction.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies using various photosensitizers, the role of p38 activation in PDT response appears to be ambiguous [29], [30], [31], [32], [33], [34]. Recently, p38 activation as a death signal has been described for the endocytically located photosensitizer TPPS2a (meso-tetraphenyl-porphine), which is applicable to photochemical internalization, a method used for release of endosomally/lysosomally trapped macromolecular drugs into the cell cytosol to enhance their biological effect in vitro [35]. We can relate our para EG-porphyrin results with these data because they exhibit similar intracellular localization and mechanism involving p38 MAPK activation in the cell death induction.…”
Section: Discussionmentioning
confidence: 99%
“…The role of MAPK activation in PDT-related oxidative cell killing has been examined in a number of recent studies using different photosensitizing agents and tumor cell types (5,39-41). However, in contrast to other oxidative challenges (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic outcome of PCI may be influenced by PDT induced cellular signaling as inhibition or activation of selected signal pathways may influence on the cytotoxic effect of the drug delivered by PCI. We have found that TPPS 2a ‐PDT mediates death and survival signaling through ERK, p38, JNK, mTOR, and EGFR 84, 97, 98, and that some of these effects have impact on the outcome of PCI of gelonin 97. PDT generated protein signal transduction may also have an impact on PCI of targeted protein toxins, as indicated for PCI of cetuximab–saporin.…”
Section: Pci Of Targeted Protein Toxinsmentioning
confidence: 98%